Facilitating EFL Speaking Skills through an English Club: Evidence from the TBI Millennial English Club - Rina Ritsna Gisma; Sahril Nur; Sultan Baa (FOSTER: Journal of English Language Teaching, 2025)
This study investigates the role of the TBI Millennial English Club in supporting students’ speaking skill development through nonformal English learning activities. Although speaking skills are essential for effective communication, many EFL learners have limited opportunities for authentic oral practice in formal classroom settings. This research aims to explore how structured English club activities facilitate students’ speaking performance, engagement, and confidence. Using a qualitative descriptive design, data were collected through direct observations of weekly club meetings and analysis of supporting documentation. The observations focused on student participation, types of speaking activities, facilitator–learner interactions, and the affective environment created during the sessions. The findings reveal three major contributions of the English club: (1) it provides consistent opportunities for authentic and meaningful speaking practice through activities such as role-plays, storytelling, discussions, and impromptu speaking; (2) facilitators play a crucial role in scaffolding learning by offering guidance, modeling target language use, and giving immediate, constructive feedback; and (3) the club fosters a supportive and motivating environment that reduces speaking anxiety and increases students’ confidence and willingness to communicate. Overall, the study concludes that the TBI Millennial English Club serves as an effective supplementary learning space that enhances students’ speaking skills and communicative competence. The implications highlight the importance of integrating nonformal speaking programs into EFL settings and providing facilitator training to maximise learning outcomes.